GAMBARAN TINGKAT PENDIDIKAN DAN PENGETAHUAN IBU TENTANG PEMBERIAN MAKANAN PENDAMPING ASI PADA BAYI DI PUSKESMAS S.PARMAN BANJARMASIN - Purwanti, Sri; Lestari, Nur Cahyani Ari (Universitas Batam, 2020)
Based on the report from the S. Parman Health Center on exclusive breastfeeding for infants aged 0-6 months, 26 out of 115 babies (22.6%) received exclusive breastfeeding. In 2019, the number of infants who received exclusive breastfeeding increased but was still far from the target coverage, which was 80%. , namely 32 babies out of 135 babies (23.7%) this is because some mothers do not know about the benefits of exclusive breastfeeding and when is the right time to give complementary feeding (MP ASI). The purpose of this study was to find out the description of the level of education and knowledge of mothers about the provision of complementary feeding to infants at the S Parman health center in Banjarmasin. This research design uses descriptive research method with a sample of 61 people taken by accidental sampling. Data were collected through questionnaire sheets and processed manually in the form of tables, then analyzed both qualitatively and quantitatively. Of the 61 respondents who gave complementary foods to breast milk, 42 people (68.9%) and those who did not provide complementary foods to infants, only 19 people (31.1%) with respondents who had basic education as many as 35 people (59.0 %), who have secondary education are 18 people (29.5%), and those who have higher education are 8 people (11.5%) and respondents who have less knowledge are 22 people (36.1%) and who have knowledge good are 19 people (31.1%), who have sufficient knowledge are 20 people (32.8%). Complementary foods that are right for the baby and the risks that may occur in giving complementary foods to breast milk are too early.